Population genetics and evolutionary history of the wild rice species Oryza rufipogon and O. nivara in Sri Lanka. Issue 23 (11th November 2018) - Sandamal, Salinda; Tennakoon, Asanka; Meng, Qing‐Lin; Marambe, Buddhi; Ratnasekera, Disna; Melo, Arthur; Ge, Song
Abstract: Genetic diversity and population genetic structure of the wild rice species Oryza rufipogon and O. nivara in Sri Lanka were studied using 33 microsatellite markers. A total of 315 individuals of 11 natural populations collected from the wet, intermediate, and dry zones of the country were used in the study. We found a moderate to high level of genetic diversity at the population level, with the polymorphic loci ( P ) ranging from 60.6% to 100% (average 81.8%) and the expected heterozygosity ( H E ) varying from 0.294 to 0.481 (average 0.369). A significant genetic differentiation between species and strong genetic structure within species were also observed. Based on species distribution modeling, we detected the dynamics of the preferred habitats for the two species in Sri Lanka and demonstrated that both O. rufipogon and O. nivara populations have expanded substantially since the last internal glacial. In addition, we showed that the geographical distribution of the two species corresponded to the climate zones and identified a few of key environmental variables that contribute to the distribution of the two species, implying the potential mechanism for ecological adaptation of these two species in Sri Lanka. These studies provided important insights into the population genetics and evolution of these wild species in Sri Lanka and are of great significance to the in situ conservation and utilization of these wild resources in genetic improvement of rice. Abstract : We provide the first report on the population genetics of two wild rice species ( Oryza rufipogon and O. nivara ). We demonstrated a high level of genetic diversity of the natural populations of the two species in Sri Lanka and explored the evolutionary history and population dynamics of the two species.